2019
DOI: 10.1088/1361-665x/ab1df3
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline-NBR blends by in situ polymerization: application as stretchable strain sensors

Abstract: Stretchable strain sensors in the form of thin films consisting of nitrile butadiene rubber (NBR)/ polyaniline (PANI) blends were prepared via in situ polymerization of aniline in the NBR solution. The sensors were characterized for thermal, morphological and piezo-electric properties. Electrical conductivity increased with an increase in filler loading. Piezo resistive measurements showed a decrease in electrical conductivity upon stretching due to disconnection mechanism between filler particles. The piezo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
(34 reference statements)
2
14
0
Order By: Relevance
“…The findings show the average number of women in Central Punjab is higher (4.09) than in Southern Punjab (3.78) and High Punjab (3.64), on average. In addition, access to school, health care, work prospects are higher in central Punjab(Irfan et al, 2019).The present study endorses social mobility as an essential feature of women's socio-cultural ability indicators(Bespinar, 2010). The experiments have been maintained in line with(Jejeebhoy & Sathar 2001;Khan & Maan, 2008).…”
supporting
confidence: 62%
“…The findings show the average number of women in Central Punjab is higher (4.09) than in Southern Punjab (3.78) and High Punjab (3.64), on average. In addition, access to school, health care, work prospects are higher in central Punjab(Irfan et al, 2019).The present study endorses social mobility as an essential feature of women's socio-cultural ability indicators(Bespinar, 2010). The experiments have been maintained in line with(Jejeebhoy & Sathar 2001;Khan & Maan, 2008).…”
supporting
confidence: 62%
“…However the characteristic peak of PVA was suppressed by the addition of PVP, and a further shift was observed in the case of CMC addition. CMC generally exhibits its characteristic peak at 22° [ 50 ] while PVP exhibits its characteristic peak at 21.84° [ 51 ]. It was observed that addition of CMC caused a slight shift in peak towards 21–22°, which shows the dominance of CMC is tricomponent composite nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…ICPs were investigated as the active material of flexible strain sensor. Because ICPs are conductive materials, their blends with a soft or elastic polymer can show a resistance sensitive to the tensile strain 102,150–153 . However, a normal ICP films on a flexible substrate usually exhibit a resistance not very sensitive to the tensile strains.…”
Section: Icps As Active Materials Of Strain Sensorsmentioning
confidence: 99%